Detection of sugar syrup adulteration in UK honey using DNA barcoding - Dodd, Sophie; Kevei, Zoltan; Karimi, Zahra; Parmar, Bhavna; Franklin, David; Koidis, Anastasios; Anastasiadi, Maria (Elsevier, 2025)
Honey is a valuable and nutritious food product, but it is at risk to fraudulent practices such as the addition of cheaper syrups including corn, rice, and sugar beet syrup. Honey authentication is of the utmost importance, but current methods are faced with challenges due to the large variations in natural honey composition (influenced by climate, seasons and bee foraging), or the incapability to detect certain types of plant syrups to confirm the adulterant used. Molecular methods such as DNA barcoding have shown great promise in identifying plant DNA sources in honey and could be applied to detect plant-based sugars used as adulterants. In this work DNA barcoding was successfully used to detect corn and rice syrup adulteration in spiked UK honey with novel DNA markers. Different levels of adulteration were simulated (1 – 30%) with a range of different syrup and honey types, where adulterated honey was clearly separated from natural honey even at 1% adulteration level. Moreover, the test was successful for multiple syrup types and effective on honeys with different compositions. These results demonstrated that DNA barcoding could be used as a sensitive and robust method to detect common sugar adulterants and confirm syrup species origin in honey, which can be applied alongside current screening methods to improve existing honey authentication tests.
Keywords: Honey; Authentication; Syrup; Adulteration; DNA marker; qPCR; 30 Agricultural, Veterinary and Food Sciences; 3006 Food Sciences; 2 Zero Hunger; Food Science; 4004 Chemical engineering